Potential of Limestone Tailings for Correction and Fertilization of an Oxisol in the Brazilian Savanna - Faria, Alvaro Jose Gomes de; Machado, Angela Franciely; Lucena, Guilherme Nunes [UNESP]; Neto, Joao Vidal de Negreiros; Carneiro, Jefferson Santana da Silva; Leite, Rubson da Costa; Silva, Rubens Ribeiro da (Taylor & Francis Inc, 2020)
Limestone mining industries produce large quantities of by-products that can generate environmental impacts if disposed inappropriately. This study aimed to evaluate the agronomic viability of limestone tailings as soil aciditys and the availability of Ca + Mg in an Oxisol. The experiment was carried out under a randomized complete design, in a 6 x 5 factorial scheme, with four replications. Six sources of limestone [Blended Limestone 1 (BL1), Unblended Limestone 1 (UL1), Blended Limestone 2 (BL2), Unblended Limestone 2 (UL2), Commercial Limestone (CC) and Pure Limestone (PL)] were studied at five application doses (0.0, 0.5, 1.0, 2.0 and 4.0 t ha(-1)). During the incubation time of the soil, it was determined the active (pH) and potential acidity (H + Al), as well as the contents of Ca + Mg. It is concluded that the maximum efficiency dose for the limestone sources BL1, UL1, BL2 and UL2 was 4.0 t ha(-1), with responses higher than or equal to commercial limestone. Thus, these sources (BL1, UL1, BL2 and UL2) can be used as soil acidity correctors, since they have adequate reactivity and neutralization power, contributing positively and promisingly in the correction of both active and potential acidity, in addition to increasing the availability of Ca and Mg.
Keywords: Soil fertility; environmental sustainability; soil acidification; beneficiation waste